Interpretation of Dispute Clauses and Liability Mechanisms for Breach of Contract in the Decision of the West Jakarta District Court no. 748/Pdt.G/2021/PN Jkt.Brt - Lydia Anindira; Gunardi Lie (AMK : Abdi Masyarakat UIKA, 2025)
This study analyzes two key legal issues in maritime transport service agreement disputes: the interpretation of dispute clauses under contract law principles and the liability and claims for damages resulting from breach of contract. The research focuses on the case between PT Cahaya Energy Farhana and PT Garuda Agung Resources, as adjudicated in West Jakarta District Court Decision No. 748/Pdt.G/2021/PN Jkt.Brt. Using normative legal research with conceptual and case study approaches, this study draws on primary sources (court decisions, Civil Code) and secondary literature. The findings show that dispute clause interpretation and contract cancellation must adhere to the principles of pacta sunt servanda and good faith (Article 1338, Civil Code). In this case, the defendant’s unilateral cancellation citing force majeure did not qualify as a compelling circumstance, as the disruption was caused by administrative negligence rather than unforeseen external factors. Moreover, liability for breach of contract, based on Article 1243 of the Civil Code, allows the aggrieved party to claim compensation for costs, losses, and interest (kosten, schaden en interesten). This decision thus sets an important precedent for applying civil liability principles in maritime contract disputes in Indonesia.